Tolerance Learning in Islamic Religious and Character Education Textbooks - Mawadda, Mita; Supriadi, Udin; Anwar, Saepul; Abbas, Hafizh Muzhaffar (Analisa: Journal of Social Science and Religion, 2023)
Islamic Religious and Character Education (hereafter PAI) textbooks are part of an important means of teaching character values, including tolerance. Some cases of intolerance are still common in Indonesia and are even associated with Islamic religious education in schools. Therefore, there is a need to review Islamic religious education in schools. This study examines the PAI materials that include tolerance learning in Islamic religious education textbooks at the 7th, 8th, and 9th grade junior high school levels. This research is important so that in the future, tolerance learning materials can be provided to students in accordance with the portions. This study uses a literature review with a qualitative approach that analyzes the content of Islamic Religious and Character Education textbooks published by the Ministry of Education and Culture of the Independent Curriculum (7th and 8th grade books) and the Revised 2013 Curriculum (9th grade books). The data obtained are then collected and analyzed using the content analysis method. The data analysis techniques in this study used 3 data analysis steps, namely: data reduction, data display, and data verification. This study shows whether there is tolerance learning in Islamic Religious Education and Character Education textbooks or not. The results of the study show that the Islamic Religious Education and Character Education textbooks at the junior high school level strongly promote tolerance.